Draft Annual Plan 2000-2001 Government of Tripura - Planning Commission (Planning Commission, 2000)
New Schemes of Annual Plan 2000-01 the Project "Upgradation of Major District Roads In Tripura" sanctioned during 1999-2000 Is likely to be revalidated during 2000-01 Tripura Agriculture Development Project with a total project cost of Rs. 40300 lakhs is likely to be sanctioned during 2000-01 Project proposal on Irrigation Schemes and Flood Management Works with a total project cost of Rs. 47565 lakhs Is likely to be sanctioned during 2000-01 Integrated Fishery Development Project In Tripura with a total project cost of Rs. 24493 lakhs Is likely to be sanctioned during 2000-01.
Government of Tripura, Planning Department